The res (restored cell structure by salinity) tomato mutant reveals the role of the DEAD‐box RNA helicase SlDEAD39 in plant development and salt response. (5th May 2020) - Capel, Carmen; Albaladejo, Irene; Egea, Isabel; Massaretto, Isabel L.; Yuste‐Lisbona, Fernando J.; Pineda, Benito; García‐Sogo, Begoña; Angosto, Trinidad; Flores, Francisco B.; Moreno, Vicente; Lozano, Rafael; Bolarín, María C.; et al.
Abstract: Increasing evidences highlight the importance of DEAD‐box RNA helicases in plant development and stress responses. In a previous study, we characterized the tomato res mutant ( restored cell structure by salinity ), showing chlorosis and development alterations that reverted under salt‐stress conditions. Map‐based cloning demonstrates that RES gene encodes SlDEAD39, a chloroplast‐targeted DEAD‐box RNA helicase. Constitutive expression of SlDEAD39 complements the res mutation, while the silencing lines had a similar phenotype than res mutant, which is also reverted under salinity. Functional analysis of res mutant proved SlDEAD39 is involved in the in vivo processing of the chloroplast, 23S rRNA, at the hidden break‐B site, a feature also supported by in vitro binding experiments of the protein. In addition, our results show that other genes coding for chloroplast‐targeted DEAD‐box proteins are induced by salt‐stress, which might explain the rescue of the res mutant phenotype. Interestingly, salinity restored the phenotype of res adult plants by increasing their sugar content and fruit yield. Together, these results propose an unprecedented role of a DEAD‐box RNA helicase in regulating plant development and stress response through the proper ribosome and chloroplast functioning, which, in turn, represents a potential target to improve salt tolerance in tomato crops. Abstract : The role in plant development and fruit yield of a chloroplast‐targeted tomato ( Solanum lycopersicum ) DEAD‐box RNA helicase, SlDEAD39, is described. We propose that other DEAD‐box RHs might be partially redundant to SlDEAD39, mediating their specific functions in salt stress response.